Investigation of oscillatory-flow behaviour across internal structure in thermoacoustic refrigeration system - Johari, Dahlia (2020)
Thermoacoustic technology has been recognised as the one of green technology as it provides alternatives green working mechanism for engine and refrigeration system. This is due to its simplicity (as there was no moving parts) and the system also use a non-polluting gas. Unfortunately, the fluid dynamics of the system is complex and not well understood. The fluid that flows inside the system is flowing in oscillatory conditions following the acoustic wave. In this study, flow distribution inside a standing wave thermoacoustic condition is tested experimentally and numerically. The thermoacoustic system is first modelled using DeltaE software. The model is used as benchmark for setting up of a thermoacoustic rig that is suitable for the investigation of the oscillatory flow behaviour across the internal structures in the thermoacoustic system. The components of the rig include the loudspeaker as the acoustic driver, a resonator made of steel and a structure known as a stack made of aluminium. The stack was a parallel-plate structure where most thermoacoustic effects take place. The test rig was build based on a quarter wavelength standing-wave thermoacoustic design. Therefore, for the purpose of investigating the fluid dynamics of oscillatory flow at different frequencies, the resonator was divided into several segments which was assembled according to flow frequency. Due to the complication of design, the study of flow frequencies was limited to only two flow frequencies, which were 14.2 Hz and 23.6 Hz. For 14.2 Hz flow frequencies, the stack was located at two different locations of 0.11λ and 0.18λ from the pressure antinode while 23.6 Hz flow frequencies, the stack was located at 0.18λ from the pressure antinode. The stack was fabricated with two different lengths of 70 mm and 200 mm. The experimental rig was first tested for resonance frequency and references point followed by the investigation of the change of velocity in each point along the thermoacoustic rig as drive ratio (ratio of pressure at antinode to the mean pressure) changes. The DeltaE software models provide pressure distribution data that are similar to the theoretical data and stack with the length of 200 mm gives a better performance in term of drive ratio (Dr) where an increment of drive ratio percentage of 28% was recorded compared to 25% drive ratio increment for the 70 mm stack. Comparisons were also made for first-order harmonic velocity amplitude, u1, obtained from three different methods; theoretical calculations, DeltaE software, and the experimentally measured values. It is found that the velocity distribution of flow across the 70 mm long stack results in highest Stoke’s Reynolds number which is 271.99 that leads to early starts of turbulence in the flow. The stack’s location of 0.11λ was also found to be the best location based on velocity data of the current flow conditions. Besides that, it is also found that 23.6 Hz flow frequency result in the better drive ratio compared to 14.2 Hz. The findings help to understand possible differences between theoretical and real experimental values so that